Brain Cortex Activity in Children With Anterior Open Bite: A Pilot Study - Restrepo, Claudia; Botero, Paola; Valderrama, David; Jimenez, Kelly; Manrique, Rubén (Frontiers in Human Neuroscience, 2020)
Anterior open bite (AOB) is related to functional alterations of the stomatognathic system. There are no studies concerning brain activation of the cortex comparing children with and without AOB during rest and activities such as deglutition and phonation. The aim of this study was to determine the activity of the brain cortex of children with AOB at rest and during phonation and deglutition, and to evaluate the association of intelligence quotient (IQ), attention (Test of Variables of Attention, known as TOVA), Beats per Minute (BPM), and oxygen saturation measurement (SpO2) with brain activity in subjects with AOB. Fourteen children (seven with AOB and seven without AOB) with mixed dentition, aged 10-13 years underwent an IQ test, TOVA, SpO2, and Quantitative Electroencephalography (QEEG). Electrodes were set in the scalp, according to the 10-20 protocol. Data was analyzed using statistical tests to assess comparisons between children with and without AOB. The results showed that neither IQ, TOVA, SpO2, or BPM showed any statistically significant differences between the groups, except for the response time (contained in TOVA) (p=0.03). Significant differences were found for the brain activity during rest (Condition 1) of the tongue, between children with and without AOB (p< 0.05 for Alpha/Theta and Alpha peak), whereas there were no differences during function (Condition 2). The findings of this investigation provides insights about the cortex activity of the brain while the tongue is in the resting position in children with AOB. This may imply an altered activity of the brain cortex, that should be considered when diagnosing and treating AOB. Other diagnostic techniques derived from investigations based on Neuroscience, could develop new diagnostic and therapeutic techniques to give better solutions to children with malocclusions. Treatments should not only be focused on the teeth, but also on the brain cortex.